The Improvement of Reliability of High-k/Metal Gate pMOSFET Device with Various PMA Conditions - Yi-Lin Yang; Wenqi Zhang; Chi-Yun Cheng; Wen-kuan Yeh (Active and Passive Electronic Components)
The oxygen and nitrogen were shown to diffuse through the TiN layer in the high-k/metal gate devices during PMA. Both the oxygen and nitrogen annealing will reduce the gate leakage current without increasing oxide thickness. The threshold voltages of the devices changed with various PMA conditions. The reliability of the devices, especially for the oxygen annealed devices, was improved after PMA treatments.